Changing sources of growth in ESOMAR anniversary year. Issue 65 (19th September 2017) - Bowman, Jo
Abstract : As ESOMAR marks its 70th anniversary, we are using our annual appraisal of the industry's performance to look behind the headline growth figures at the forces that have shaped – and are shaping – both the work we do and the reasons we do it.